2001
DOI: 10.1093/nar/29.4.928
|View full text |Cite
|
Sign up to set email alerts
|

Response of human DNA polymerase iota to DNA lesions

Abstract: Lesion bypass is an important mechanism to overcome replication blockage by DNA damage. Translesion synthesis requires a DNA polymerase (Pol). Human Pol iota encoded by the RAD30B gene is a recently identified DNA polymerase that shares sequence similarity to Pol eta. To investigate whether human Pol iota plays a role in lesion bypass we examined the response of this polymerase to several types of DNA damage in vitro. Surprisingly, 8-oxoguanine significantly blocked human Pol iota. Nevertheless, translesion DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 39 publications
9
114
2
1
Order By: Relevance
“…2). Although the incorporation of 2'-deoxyribonucleotides opposite 8-OH-Gua in template DNA by DNA pol ι in vitro was reported [31][32][33], the result obtained in this study suggests that the contribution of the DNA pol to 8-OH-Gua bypass is minimal, at best, at least in this human cell line. REV1 is a member of the Y-family DNA pols, but it acts as deoxycytidyl transferase opposite a range of damaged bases [23,24].…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…2). Although the incorporation of 2'-deoxyribonucleotides opposite 8-OH-Gua in template DNA by DNA pol ι in vitro was reported [31][32][33], the result obtained in this study suggests that the contribution of the DNA pol to 8-OH-Gua bypass is minimal, at best, at least in this human cell line. REV1 is a member of the Y-family DNA pols, but it acts as deoxycytidyl transferase opposite a range of damaged bases [23,24].…”
contrasting
confidence: 58%
“…It has been shown that TLS DNA pols bypassed 8-OH-Gua in vitro [25][26][27][28][29][30][31][32][33][34]. Thus, to understand the mutagenesis and carcinogenesis processes by 8-OH-Gua, it is important to examine the contributions of the polymerases to the induction and suppression of the G:CT:A mutations caused by this lesion in living mammalian cells.…”
Section: -Oh-gua Is Highly Mutagenic and Induces G:ct:a Transversiomentioning
confidence: 99%
“…5D). Several in vitro experiments have indicated that the Pol protein participates in the bypass of two major UV-induced DNA lesions, CPDs and pyrimidine pyrimidone photoproducts [(6-4)PPs] (27,60,(63)(64)(65)76). According to these previous studies, Pol protein bypasses thymine-thymine CPDs in a highly error-prone manner under certain conditions (60,63,64).…”
Section: Role For Pol In Prevention Of Uv-induced Mesenchymal Tumorsmentioning
confidence: 99%
“…Studies using in vitro replication systems have revealed that the three related Y family enzymes, pols η (Rad30A), ι (Rad30B) and κ (DinB1), are capable of bypassing various DNA lesions [e.g. [28][29][30][31][32][33][34][35][36] that are normally blockers of classical DNA polymerases such as pol α and pol β. However, such translesion syntheses can be error-free or error-prone.…”
Section: 3-bis(2-chloroethyl)-1-nitrosourea (Bcnu) Is An Effective mentioning
confidence: 99%
“…29,34,[41][42][43]. A unique feature of this enzyme is that it preferentially incorporates G, rather than A, opposite the template T, leading to a T:G mismatch [29,43,44].…”
Section: Error-prone Nucleotide Incorporation Opposite Ea or εA By Humentioning
confidence: 99%